Targeting Chemokine Receptor CCR1 as a Potential Therapeutic Approach for Multiple Myeloma - Gilchrist, Annette; Echeverria, Stephanie L. (Frontiers in Endocrinology, 2022)
Multiple myeloma is an incurable plasma B-cell malignancy affecting 6.5 per 100,000 people in the U.S. with 5-year survival rates approximately 10-30% lower than other hematologic cancers. Treatment options include combination chemotherapy followed by autologous stem cell transplantation. However, not all patients are eligible for autologous stem cell transplantation, and current pharmacological agents are limited in their ability to reduce tumor burden and extend MM remission times. The “chemokine network”, chemokines and their cognate receptors, present in the normal bone microenvironment and tumor microenvironment of multiple myeloma. Chemokine-receptor 1 (CCR1) antagonists may provide a novel approach for treating multiple myeloma. In vitro CCR1 antagonists display a high degree of specificity, and in some cases signaling bias. In vivo studies have shown they can reduce tumor burden, minimize osteolytic bone damage, deter metastasis, and limit disease progression in MM models. While multiple CCR1 antagonists have entered the drug pipeline, none have entered clinical trials for treatment of multiple myeloma. This review will discuss whether current CCR1 antagonists are a viable treatment option for multiple myeloma, and studies aimed at identifying which CCR1 antagonist(s) are most appropriate for this disease.